Ag-Ag2O nanocomposite biosynthesis by mixed bacterial cultivation and effect of the ph on size and optical properties of the nanocomposite - Morad G. S. S. Al-Asbahi; Bashir A. Al-Ofiri; Fuad A. A. Saad; Adnan Alnehia; Muhammad Hadi (Journal of Materials Science: Materials in Medicine, 2025)
Abstract This study examines the influence of pH on the energy band gap and crystallite size during the synthesis of a novel Ag-Ag2O nanocomposites through the mixed cultivation of Lactobacillus sp. and Bacillus sp. A range of analytical techniques, including X-ray Diffraction (XRD), UV-visible Spectroscopy (UV-vis), Fourier Transform Infrared Spectroscopy (FTIR), and Transmission Electron Microscopy (TEM), were employed to investigate the structural and optical characteristics of the nanocomposites. XRD analysis confirmed the presence of cubic phases of Ag and Ag2O, with crystallite sizes varying from 8 to 44 nm; notably, smaller crystallites were observed at a pH of 6.5. UV-vis spectroscopy indicated an energy band gap ranging from 1.83 to 1.897 eV, suggesting promising applications for the material. The optimal pH for synthesis, which yielded the smallest particle size as verified by TEM, was identified as 6.5. FTIR analysis revealed the presence of biologically derived coating agents that may enhance the immutability and bioactivity of the nanocomposite. Antibacterial assays demonstrated significant efficacy against Enterococcus faecalis(E. faecalis) and Escherichia coli, particularly highlighting its effectiveness against E. faecalis. Hemolytic assays confirmed the biocompatibility of the nanocomposite at lower concentrations. These findings indicate the potential applications of the biogenic Ag-Ag2O nanocomposites in medical and environmental fields, offering a sustainable solution to challenges associated with bacterial contamination. Future research may focus on integrating these biologically synthesized nanoparticles into advanced materials and coatings to improve their performance. Graphical Abstract